PENGARUH ADANYA TEMPAT WISATA TERHADAP KESEJAHTERAAN DAN PENDAPATAN UKM KECIL DISEKITAR TEMPAT WISATA DESA SANANREJO, KECAMATAN TUREN KABUPATEN MALANG - Anindya Veradina; Abdul Wahid Mahsuni; Muhammad Cholid Mawardi (Universitas Islam Malang, 2018)
ABSTRACTThe development of Sananrejo Village tourism area has the potential toprovide business opportunities for the surrounding communities. SananrejoVillage tourism object is located in Sananrejo Village, Turen District, MalangRegency. The success of tourism objects is very dependent on the important roleof the surrounding community. This study aims to analyze the level of welfare ofSMEs who use the services of Sananrejo Village tourism objects and analyze thefactors that influence the level of income of SMEs who use the services ofSananrejo Village tourism objects. Data analysis includes descriptive analysis,multiple linear regression analysis and SUSENAS-BPS welfare indicator analysis.The results showed that factors affecting the welfare of SMEs were income,expenditure, education, health, housing conditions, and home facilities. While thefactors that influence welfare are, age, education, number of family members,expenses, and work time. Based on the level of welfare of most SMEs that useSananrejo Village tourism objects, have a moderate level of welfare with apercentage of 43%, then a high level of welfare with a percentage of 31% and thesmallest is a low level of welfare with a percentage of 26%. Then based on theincome level of most SMEs that utilize Sananrejo Village tourism objects, have amoderate income level with a percentage of 58%, then a high income level with apercentage of 33% and the smallest is a low income level with a percentage of 9%Keywords: Sananrejo Village Tourism Object, Prosperity, Revenue